Bone Loss in the Acute Stage Following Burn Injury - Original Investigation - Berrin Leblebici; Mehmet Adam; Akın M. Tarım; Nafiz M. Akman; Mehmet A. Haberal (Galenos Yayinevi, 2007)
Aim: The purpose of this study was to determine whether a bone loss occurs during acute period following burn injury or not, and to investigate the effects of various parameters on it. Materials and Methods: This study was conducted on 19 patients, ages between 20 and 50, who had a burn injury with more than %20 of Total Body Surface Area (TBSA). We recorded the patients' burn cause, localization, percantage, ambulation and functional status. At the end of the first month, we measured bone mıneral densıty of total L1-L4 vertebrae, left distal forearm, left total femur, in all patients. A Z score less than -1 was accepted to be the indicator of bone loss. Results: The mean age of the patients (14 male and 5 female) was 33.09±11.61. We found a Z score less then -1 in 68.4% of left distal forearm, 21.1% of left total femur and 36.8% of total L1-L4 vertabrae measurements. There were no significant correlations between TBSA, Functional Ambulatıon Scale and Functional Independence Measure, and Z scores. Conclusion: There is a reduction in Bone Mineral Density in patıents wıth moderate/severe burn ınjuries in the acute period which is not correlated wıth neither TBSA nor functional status. (From the World of Osteoporosis 2007;13:33-6)